Color variability and relationship with basic density and extractive content of Calycophyllum spruceanum wood - Silva, Sandra Bezerra da; Andrade, Jaily Kerller Batista de; Arantes, Marina Donária Chaves; Silva, João Gabriel Missia da; Brocco, Victor Fassina; Paes, Juarez Benigno (Floresta, 2019)
There are reports relating color to extractives, however there is a lack of information about the effect of other characteristics on the colorimetry of wood. Thus, this study aimed to evaluate the longitudinal and radial variability of color and its relationship with the basic density and extractive contents of Calycophyllum spruceanum wood from a six-year-old plantation located in Rio Branco, Acre, Brazil. The determination and assessment of the wood color were carried out by the Commission Internationale de L’Éclairage - CIE-L*a*b* system. The basic density and extractive contents were determined according to current technical standards. The species wood color was classified as yellowish olive. The highest and lowest lightness (L*) were longitudinally observed in the base (cutting height) and diameter at breast height (DBH), taken at 1.30 m from the ground. In relation to radial position, the lightness (L*) was lower in peripheral regions of the trunk. Higher concentrations of redness (a*) and yellowness (b*) and saturation (C) occurred along the DBH and the external radial position. In evaluating age, the extractive contents were not correlated to the wood color, while the basic density was correlated with a*, b*, C and h* colorimetric parameters. The colorimetric characterization of this specie contributes to its proper identification and a more homogeneous classification of lumber, and can be used from the log break-down (sawing) to its end use, adding commercial value to the wood.